2003
DOI: 10.1097/01.md.0000091181.93122.55
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality in Systemic Lupus Erythematosus During a 10-Year Period

Abstract: In the present study, we assessed the frequency and characteristics of the main causes of morbidity and mortality in systemic lupus erythematosus (SLE) during a 10-year period and compared the frequency of early manifestations with those that appeared later in the evolution of the disease. In 1990, we started a multicenter study of 1,000 patients from 7 European countries. All had medical histories documented and underwent medical interview and routine general physical examination when entered in the study, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
212
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,142 publications
(228 citation statements)
references
References 31 publications
2
212
2
7
Order By: Relevance
“…The overall prevalence rate of lupus nephritis was higher in the current study compared to notable surveys [22,23]. It is noteworthy that previous studies have suggested that the highest rate of renal involvement in the world (73%) was found in Indo-Asians [16,24].…”
Section: Discussion ___________________________contrasting
confidence: 35%
“…The overall prevalence rate of lupus nephritis was higher in the current study compared to notable surveys [22,23]. It is noteworthy that previous studies have suggested that the highest rate of renal involvement in the world (73%) was found in Indo-Asians [16,24].…”
Section: Discussion ___________________________contrasting
confidence: 35%
“…Therapeutic options for CTD have been less than satisfactory; anti-inflammatories and immunosuppressants have been the primary focus since no cure is known at this time. Long-term immunosuppressants and anti-inflammatories carry significant morbidity, estimated mortality is 6.8% while the most frequent predictors are: active SLE, thromboses, and infections, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-y survival rate of patients with lupus-associated glomerulonephritis increased from 44% in the 1950s to 82% recently (2). Despite clear advances in the treatment of this autoimmune disease, the mean age of death of patients dying from systemic lupus erythematosus is 44 y (3).…”
mentioning
confidence: 99%